2013
DOI: 10.1038/eye.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Vertical muscle transposition augmented with lateral fixation (Foster) suture for Duane syndrome and sixth nerve palsy

Abstract: Purpose To report the postoperative results of full-tendon vertical rectus transposition (VRT) augmented with lateral fixation suture for the treatment of type 1 Duane syndrome and sixth nerve palsy and to determine whether there was a decrease in the effect of the Foster suture over time. Methods This retrospective, consecutive case series included patients who underwent a full-tendon VRT transposition with lateral fixation for type 1 Duane syndrome or sixth nerve palsy. The primary outcome measures included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
0
22
0
4
Order By: Relevance
“…In the literature, much has been written about the most common DRS form (type 1) (7,10,11). However there are only few studies about type 2 DRS, and this is the first study to discuss the clinical features and management of pediatric DRS type 2 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, much has been written about the most common DRS form (type 1) (7,10,11). However there are only few studies about type 2 DRS, and this is the first study to discuss the clinical features and management of pediatric DRS type 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular deviation in the primary position of gaze was measured using a cover test with the uninvolved eye fixed on a target. Abnormal head posture (AHP) was estimated for all patients while the patient sat erect, fixating on a target 20 feet distant as previously described (7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Diese Modifikation verbesserte deutlich die primäre Position und Abduktion ohne eine zusätzliche Rücklagerung des ipsilateralen M. rectus medialis, was die Durchblutung des Vorderabschnitts schont und das Risiko einer Vorderabschnittsischämie minimalisiert. Yazdian [12], Akar [13], del Pilar Gonzáles [3] Methods and Results Full tendon transpositions of vertical rectus muscles augmented with posterior fixation suture was performed in 2014 on five patients with abducens nerve palsy. Two of the patients received Botox injections in the medial rectus muscle: one of them three months after the surgery and another during the surgery.…”
Section: Abstract Introductionunclassified
“…We read with interest the article by Akar et al 1 We would like to make the following observations/queries.…”
mentioning
confidence: 99%
“…It has been suggested that vertical rectus transposition (VRT) may worsen retraction and shoots. 2,3 Thus an objective measurement (pre-and postoperative) of palpebral aperture changes and shoots is in order, more so with augmented transposition as in Akar et al 1 Also, the confirmation of absence of anomalous LR innervation pre-operatively is essential. This may be assessed by the Romero-Apis force degeneration test 4 or, as suggested by some, by electromyography.…”
mentioning
confidence: 99%